Phosphorus Management and Water Quality Problems in Grazingland Ecosystems - Maria L. Silveira; Joao M. B. Vendramini; Lynn E. Sollenberger (International Journal of Agronomy)
Phosphorus management in grazingland ecosystems represents a major challenge of agronomic and environmental importance. Because of the extensive acreage occupied by grazinglands, decisions concerning pasture fertilization and nutrient management in forage-based livestock systems are crucial to both farmers and regulatory agencies. The purpose of this paper is to provide an overview of the literature relevant to pasture P fertilization and the potential impacts on water quality. There continue to be uncertainties regarding interrelationships between pasture management and water quality issues. Despite the extensive body of literature on nutrient transport from grazinglands, limited information is available on the relationships between land use, transport potential, water management, and climatic conditions affecting nutrient losses at a watershed scale. As agriculture continues to modernize and intensify, public concerns about the impacts of plant nutrients on environmental quality will likely increase. Managing water quality protection and profitable agriculture will be a major challenge for the next generations.